Horrendous evils and the goodness of God - Adams, Marilyn McCord (1999)
"When confronted by horrendous evil, even the most pious believer may question not only life's worth but also God's power and goodness. A distinguished philosopher and a practicing minister, Marilyn McCord Adams has written a highly original work on a fundamental dilemma of Christian thought - how to reconcile faith in God with the evils that afflict human beings." "If redirected, philosophical reflection on evil can, Adams's book demonstrates, provide a valuable approach not only to theories of God and evil but also to pastoral care. Drawing on the resources of Biblical religion, her work invites thoughtful readers to reconsider their notions of this eternal question and demonstrates how horrendous evils can indeed be defeated by the goodness of God."--Jacket.
Part One. Deconstructing a problem -- Problems of Evil -- Global Goodness and Its Limitations -- Dignity of Human Nature? -- Part Two Conceptual enrichments -- Divine Agency, Remodeled -- Purity and Defilement -- Symbolic Value: Honor and Shame -- Taste and See ... -- Part Three Resolution and Relevance -- Resources to the Rescue -- Praxis of Evil -- Conclusion: Horrors, Disruptive and Disrupting.
Includes bibliographical references (unnumbered page 209-page 214) and index.
Keywords: Good and evil; Theodicy